Edukasi Penyuluhan Pentingnya ASI Eksklusif Untuk Mencegah Penyakit Stunting - Aam Linda Nurfalah; Dina Selvia; Sari Oktavia Depyanti; Popi Sopiah (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
Introduction: Stunting is a condition that occurs when toddlers experience a lack of nutritional intake for a long period of time, thus inhibiting growth and causing the child's height to be shorter than the standard. Stunting can be caused by giving complementary foods (MP-ASI) before the age of six months and not giving Exclusive Breastfeeding to babies. Methodology: The method used is the lecture method, accompanied by leaflet media to 34 participants. To assess knowledge, a pre-post test was conducted. Results: The health education carried out showed positive results as seen from the results of the post-test scores which were better than the results of the pre-test scores.